A Comparative Study on the Amount of Extruded Material from the Apical Foramen with NiTi Rotary and Stainless Steel Hand Instruments - Nazari, Shahrzad; MirMotalebi, Farshid (Iranian Endodontic Journal, 2008)
INTRODUCTION: The purpose of the present study was to quantify and compare the amount of extruded debris from apical foramen after instrumentation of the root canal system with hand and rotary instruments. MATERIALS AND METHODS: Root canals of forty five fresh extracted single rooted human teeth with mature apexes and less than 15 degree of root curvature were instrumented in group A with stainless steel K-Type files, in group B with rotary NiTi Flex Master files, and in group C with rotary NiTi ProTaper files and followed weighting the extruded debris by a digital scale to within 0.0001 gram accuracy. RESULTS: In all groups, the mean weight of extruded debris was not more than 5 mg (P=0.0l) and was ranked as: Group A>Group B>Group C. There were statistically significant differences among three groups (p=0.0l). The mean value of extruded debris in the ProTaper and Flex Master groups were 0.652 and 0.788 mg, respectively. CONCLUSION: The study revealed that the amount of extruded debris from the apical foramen was minimal when ProTaper files were used.